A log aggregation forensic analysis framework for cloud computing environments. Issue 7 (July 2017) - Ahmed Khan, Muhammad Naeem; Ullah, ShahWali
Abstract : Cloud computing has emerged in the past decade to provide wide-ranging computational facilities at cheaper cost. Cloud computing facilitates the sharing of processing units, storage devices and applications. The National Institute of Standards and Technology describes cloud computing as a model for facilitating on-demand ubiquitous network access to a combined pool of computing resources – eg, networks, storage, servers, services and applications. These resources can easily be provisioned and released without the service provider's interaction. Cloud computing is now in widespread use. But it does pose a number of security challenges. Muhammad Naeem Ahmed Khan and ShahWali Ullah of the Shaheed Zulfikar Ali Bhutto Institute of Science and Technology propose an analysis model based on aggregating available logs from clients and servers that could help identify and detail suspicious activity on cloud-based systems.